Association of Human iPSC Gene Signatures and X Chromosome Dosage with Two Distinct Cardiac Differentiation Trajectories - Agnieszka D'Antonio-Chronowska (Stem Cell Reports, 2019)
Summary: Despite the importance of understanding how variability across induced pluripotent stem cell (iPSC) lines due to non-genetic factors (clone and passage) influences their differentiation outcome, large-scale studies capable of addressing this question have not yet been conducted. Here, we differentiated 191 iPSC lines to generate iPSC-derived cardiovascular progenitor cells (iPSC-CVPCs). We observed cellular heterogeneity across the iPSC-CVPC samples due to varying fractions of two cell types: cardiomyocytes (CMs) and epicardium-derived cells (EPDCs). Comparing the transcriptomes of CM-fated and EPDC-fated iPSCs, we discovered that 91 signature genes and X chromosome dosage differences are associated with these two distinct cardiac developmental trajectories. In an independent set of 39 iPSCs differentiated into CMs, we confirmed that sex and transcriptional differences affect cardiac-fate outcome. Our study provides novel insights into how iPSC transcriptional and X chromosome gene dosage differences influence their response to differentiation stimuli and, hence, cardiac cell fate. : In this article, D'Antonio-Chronowska, Donovan and colleagues differentiated 191 iPSC lines to generate iPSC-derived cardiovascular progenitor cells (iPSC-CVPCs). The iPSC-CVPC samples showed cellular heterogeneity due to varying fractions of cardiomyocytes (CMs) and epicardium-derived cells (EPDCs). Donor sex and expression levels of signature genes in iPSCs played a role in the relative proportions of CMs and EPDCs present in the derived CVPCs. Keywords: iPSC, iPSC-derived cardiovascular progenitor cells, iPSC-derived cardiomyocytes, iPSC-derived epicardium, scRNA-seq, single-cell transcriptomics, X chromosome inactivation, X chromosome erosion, iPSC differentiation